2018
DOI: 10.1590/01047760201824032561
|View full text |Cite
|
Sign up to set email alerts
|

ENERGY AND MASS BALANCE IN THE PYROLYSIS PROCESS OF Eucalyptus WOOD

Abstract: The process was carried out using an innovative pyrolysis technology, the Macro ATG oven. Moisture contents (0.83 and 13%) have a low infl uenced the charcoal yields. The gas peak begins 120 minutes after pyrolysis ignition, this is the best period for burning gases. 53% of the total energy of the process was concentrated in the charcoal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Pyrolysis of wood consists in the heating of wood to temperatures of up to 500°C in a nonoxidizing atmosphere and has as one of its products a solid material rich in carbon, called charcoal. Its volatile fraction consists of non-condensable and condensable gases, which compose the pyroligneous liquid (Jesus et al, 2018;Demirbas, 2003;Guillén et al, 2001). Pyrolysis is a complex process that consists of a series of chemical reactions, accompanied by heat and mass transfer (Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis of wood consists in the heating of wood to temperatures of up to 500°C in a nonoxidizing atmosphere and has as one of its products a solid material rich in carbon, called charcoal. Its volatile fraction consists of non-condensable and condensable gases, which compose the pyroligneous liquid (Jesus et al, 2018;Demirbas, 2003;Guillén et al, 2001). Pyrolysis is a complex process that consists of a series of chemical reactions, accompanied by heat and mass transfer (Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“… 18 21 The energy and mass balance in the pyrolysis process of eucalyptus wood were also reported to optimize the technologies. 22 A life cycle assessment study also demonstrated that the production of bio-oil and activated carbon using a fast pyrolysis process is an eco-friendly option for eucalyptus wood waste management. 23 …”
Section: Introductionmentioning
confidence: 98%
“…Pyrolysis is one of the advanced bioenergy conversion technologies, which rapidly and efficiently converts the solid biomass waste into high energy density fuel products or materials by thermochemical conditions. The products of the biomass pyrolysis process typically includes bio-oil, char, and gases, and bio-oil can be upgraded into biofuels or used to make value-added chemicals, while char is a good feedstock of activated carbon, soil amendment, and functional carbonaceous functional materials, and gases can be burned for energy recovery or used to produce syngas. In view of its large quantity, eucalyptus wood was selected and studied as the raw biomass feedstock of the pyrolysis process for the production of bio-oil and biochar. Eucalyptus wood samples were initially pyrolyzed on a laboratory-scale pyrolysis system at different operating conditions in the ranges of 300–800 °C and 0.050–0.300 L min –1 , and the results show that bio-oil derived from eucalyptus wood may be useful for the production of alternative liquid fuels and fine chemicals . Fast pyrolysis of eucalyptus wood was carried out using different reactor configurations and scale setups. The energy and mass balance in the pyrolysis process of eucalyptus wood were also reported to optimize the technologies . A life cycle assessment study also demonstrated that the production of bio-oil and activated carbon using a fast pyrolysis process is an eco-friendly option for eucalyptus wood waste management …”
Section: Introductionmentioning
confidence: 99%
“…5 While pyrolysis offers an effective route to convert the plastic, the waste stream must be dried prior to conversion often reducing the energy balance substantially. 6 This is particularly true of wet feedstock's such as food wastes. A more effective route for processing wet food wastes is through hydrothermal liquefaction (HTL), where the slurry is processed between 270 and 350 °C, keeping the water in the liquid phase under pressure, resulting in a biocrude, aqueous phase, and solid residue.…”
Section: Introductionmentioning
confidence: 99%
“…While pyrolysis offers an effective route to convert the plastic, the waste stream must be dried prior to conversion often reducing the energy balance substantially . This is particularly true of wet feedstock’s such as food wastes.…”
Section: Introductionmentioning
confidence: 99%